QUANTITATIVE STANDING, OUT-OF-THE PLACE, AND IRRESOLUTION IN JAMES JOYCE’S A LITTLE CLOUD, AFTER THE RACE, AND EVELINE - Zaid Tayyeh Mohammed (European Journal of Humanities and Educational Advancements, 2024)
This paper takes into consideration three selected short stories of James Joyce’s Dubliners, A little Cloud, After the Race, and Eveline. One aspect that unites these disparate stories in Dubliners is shared themes. All the stories are united by the idea that tales dramatize: paralysis, corruption, and death. In these tales characters fail to move ahead, instead they move outward and then retreat, or else circle endlessly. I tend to analyze how characters stand in the worldly pursuits and the watchful concern over how they stand is disturbing to their everyday life controls them; in order to maintain their standing, these characters must do what others approve of, praise, command and require, this is called other-directedness by Martin Heidegger. In A little Cloud, a clerk meets his successful friend and influenced by him fantasizes about succeeding himself. In After the Race, we witness how a 26-year-old Irishman named Jimmy, who is half-baked membership in the group, struggles to be part of a class which is not compatible with his. In Eveline, Eveline Hill, a 19-yearold woman who wants to embark on a journey out of Ireland, but she cannot move, she is fettered by conventions though. This study aims to show the reality by which these characters live is a social restriction, however, there is no evident resolution in each of these three stories, and the epiphany as a positive quality of these works contributes to this restrictedness.